Castles from the Rożnów and Czchów lakes area as geotouristic lapidarium and role of the Istebna Sandstones in their construction - Cieszkowski, Marek; Waśkowska, Anna (Geotourism/Geoturystyka)
On the Rożnów Foothils area, at the Rożnów and Czchów artificial lakes, a few usually ruined castles are located. This historical and recently monumental defensive objects emerged mainly in the Middle Ages. These Castles, are located on exposures of the Upper Cretaceous Istebna Beds. The Istebna Sandsones constitutes also natural local construction raw materials. The Istebna Beds are involved in the structure of the Silesian Nappe, one of the main Outer Carpathian tectonic units. The original walls of castles with their geological enclosing are geoturistic attractions of the Rożnów Land. They could be also a kind of lapidarium. In their walls are exposed specimens of the sandstone lithotypes typical for the Istebna Beds.